The efficacy of health education practices on smoking cessation behaviour of women in a public training center - Gölbaşı, Zehra; Levent, Sevim (Journal of Dependence, 2008)
Objective: This study was carried out to determine the efficacy of health education practices on smoking cessation behavior of women in a public training center. Method: This research was conducted at a public training center. It was interviewed 285 women attended to public training center and it was found that 64 women smoked. The sample was consisted of 47 women because 17 women left from the course. A questionnaire was used to describe individual characteristics and smoking behavior of women. Then, it was conducted some health education practices regarding smoking cessation along nine weeks. It was determined the smoking behavior of women at first and fourth month after finishing the interventions. Results: It was found that smoking rate was 22.4 % among women attended at public training center. After the interventions at first month, it was interviewed 47 women who had smoked and 12 of them (25.5%) stated that stopped smoke. It was interviewed all women (47 women) at the second evaluation that was done at forth month after the interventions. It was found that one women who stopped smoke at first month have started smoke again and 11 women have continued don’t smoke (23.4%). This difference between smoking rate of women at before intervention and forth month smoke rate was statistically significant (p<0.001). Conclusion: The health education practices that conducted by nurse students affected the smoking rate of women. However, it is needed research about whether this effect is permanent or not.